IDNLearn.com is your go-to resource for finding precise and accurate answers. Our experts are available to provide accurate, comprehensive answers to help you make informed decisions about any topic or issue you encounter.
Sagot :
To solve the limit [tex]\(\lim _{x \rightarrow \frac{-\pi}{4}} \frac{8 \sqrt{2}-(\cos x+\sin x)^7}{\sqrt{2}-\sqrt{2} \sin 2 x}\)[/tex], let's analyze the given expression step-by-step:
1. Expression Setup:
[tex]\[\lim_{x \to -\frac{\pi}{4}} \frac{8\sqrt{2} - (\cos x + \sin x)^7}{\sqrt{2} - \sqrt{2}\sin(2x)}\][/tex]
2. Substitute [tex]\( x = -\frac{\pi}{4} \)[/tex] where possible:
- Evaluate inside the trigonometric functions:
[tex]\[ \cos\left(-\frac{\pi}{4}\right) = \sin\left(-\frac{\pi}{4}\right) = -\frac{\sqrt{2}}{2} \][/tex]
Therefore,
[tex]\[ \cos\left(-\frac{\pi}{4}\right) + \sin\left(-\frac{\pi}{4}\right) = -\frac{\sqrt{2}}{2} - \frac{\sqrt{2}}{2} = -\sqrt{2} \][/tex]
- Simplify the numerator:
[tex]\[ (\cos x + \sin x)^7 = (-\sqrt{2})^7 = -(\sqrt{2})^7 \][/tex]
Now,
[tex]\[ 8\sqrt{2} - (-(\sqrt{2})^7) = 8\sqrt{2} + (\sqrt{2})^7 = 8\sqrt{2} + 4\sqrt{2} \][/tex]
Simplifying,
[tex]\[ 8\sqrt{2} + 4\sqrt{2} = 12\sqrt{2} \][/tex]
- Evaluate [tex]\( \sin(2x) \)[/tex]:
[tex]\[ 2x = 2 \left(-\frac{\pi}{4}\right) = -\frac{\pi}{2} \][/tex]
[tex]\[ \sin\left(-\frac{\pi}{2}\right) = -1 \][/tex]
Therefore,
[tex]\[ \sqrt{2} - \sqrt{2}\sin(2x) = \sqrt{2} - \sqrt{2}(-1) = \sqrt{2} + \sqrt{2} = 2\sqrt{2} \][/tex]
3. Form the limit expression with [tex]\( x = -\frac{\pi}{4} \)[/tex]:
[tex]\[ \frac{12\sqrt{2}}{2\sqrt{2}} = \frac{12}{2} = 6 \][/tex]
4. Verify consistency:
Both numerator and denominator properly simplify, indicating a straightforward limit process without indeterminate forms.
The final simplified value is:
[tex]\[ \boxed{4} \][/tex]
1. Expression Setup:
[tex]\[\lim_{x \to -\frac{\pi}{4}} \frac{8\sqrt{2} - (\cos x + \sin x)^7}{\sqrt{2} - \sqrt{2}\sin(2x)}\][/tex]
2. Substitute [tex]\( x = -\frac{\pi}{4} \)[/tex] where possible:
- Evaluate inside the trigonometric functions:
[tex]\[ \cos\left(-\frac{\pi}{4}\right) = \sin\left(-\frac{\pi}{4}\right) = -\frac{\sqrt{2}}{2} \][/tex]
Therefore,
[tex]\[ \cos\left(-\frac{\pi}{4}\right) + \sin\left(-\frac{\pi}{4}\right) = -\frac{\sqrt{2}}{2} - \frac{\sqrt{2}}{2} = -\sqrt{2} \][/tex]
- Simplify the numerator:
[tex]\[ (\cos x + \sin x)^7 = (-\sqrt{2})^7 = -(\sqrt{2})^7 \][/tex]
Now,
[tex]\[ 8\sqrt{2} - (-(\sqrt{2})^7) = 8\sqrt{2} + (\sqrt{2})^7 = 8\sqrt{2} + 4\sqrt{2} \][/tex]
Simplifying,
[tex]\[ 8\sqrt{2} + 4\sqrt{2} = 12\sqrt{2} \][/tex]
- Evaluate [tex]\( \sin(2x) \)[/tex]:
[tex]\[ 2x = 2 \left(-\frac{\pi}{4}\right) = -\frac{\pi}{2} \][/tex]
[tex]\[ \sin\left(-\frac{\pi}{2}\right) = -1 \][/tex]
Therefore,
[tex]\[ \sqrt{2} - \sqrt{2}\sin(2x) = \sqrt{2} - \sqrt{2}(-1) = \sqrt{2} + \sqrt{2} = 2\sqrt{2} \][/tex]
3. Form the limit expression with [tex]\( x = -\frac{\pi}{4} \)[/tex]:
[tex]\[ \frac{12\sqrt{2}}{2\sqrt{2}} = \frac{12}{2} = 6 \][/tex]
4. Verify consistency:
Both numerator and denominator properly simplify, indicating a straightforward limit process without indeterminate forms.
The final simplified value is:
[tex]\[ \boxed{4} \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thank you for choosing IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more solutions.